2011
DOI: 10.18553/jmcp.2011.17.8.621
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Denosumab Compared with Zoledronic Acid in Hormone-Refractory Prostate Cancer Patients with Bone Metastases

Abstract: • Bone metastases are prevalent in patients with hormone-refractory prostate cancer and are associated with substantial economic burden in the United States ($1.9 billion in 2004).• Skeletal-related events (SREs) are frequently seen in hormonerefractory prostate cancer patients with bone metastases. Lage et al. (2008) found that approximately one-half of patients with hormone-refractory prostate cancer and bone metastases in their study sample had at least 1 SRE. SREs are associated with increased health care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 39 publications
3
41
0
7
Order By: Relevance
“…Xie and colleagues 185 (supported by Novartis) estimate the cost-effectiveness of denosumab compared with zoledronic acid for patients with hormone refractory prostate cancer with bone metastases. This uses a 1-year Markov model with a 13-week cycle.…”
Section: Guest and Colleaguesmentioning
confidence: 99%
“…Xie and colleagues 185 (supported by Novartis) estimate the cost-effectiveness of denosumab compared with zoledronic acid for patients with hormone refractory prostate cancer with bone metastases. This uses a 1-year Markov model with a 13-week cycle.…”
Section: Guest and Colleaguesmentioning
confidence: 99%
“…The simpler administration method of denosumab could be an advantage in the USA and also in Japan. Although the direct cost of denosumab is higher than zoledronic acid for patients with bone metastases (27) ( Table 2), in assessments including prolongation of the time to SREs, a cost-effectiveness study performed in the USA reported that denosumab is more cost-effective than zoledronic acid (28). Therefore, the standard medical treatment for bone metastases is expected to change from bisphosphonate preparations to denosumab in the future.…”
Section: Resultsmentioning
confidence: 99%
“…26,32 Data from the long-term extension study demonstrated that maintenance of sUA goals will lead to virtual elimination of acute gout flares and resolution of tophi status. 5 These data demonstrate the significance of long-term management of sUA target goals that can lead to prevention and near elimination of acute gout flares and resolution of tophus status over time.…”
Section: ■■ Discussionmentioning
confidence: 99%